A constraint-programming-based approach for solving the data dissemination problem. (February 2017) - Bocquillon, Ronan; Jouglet, Antoine
Abstract: Systems of mobile Systems are intermittently connected networks that use store-carry-forward routing for data transfers. Independent systems collaborate and exchange data to achieve a common goal. Data transfers are only possible between systems that are close enough to each other, when a so-called contact occurs. During a contact, a sending system can transmit to a receiving system a fixed amount of data held in its interna then assume it holds at a til buffer. We assume that the trajectories of component systems are predictable, and consequently that a sequence of contacts may be considered. This dissemination problem is aimed at finding a transfer plan such that a set of data can be transferred from a given subset of source systems to all the recipient systems. In this paper, we propose an original constraint-programming-based algorithm for solving this problem. Computational results show that this approach is an improvement on the integer-linear-programming-based approach that we proposed in a previous paper. Abstract : Highlights: We study the problem of transferring data through an intermittently connected network. We propose a constraint programming approach to solve the problem. We propose lower bounds and symmetry breaking techniques. We provide experimental results showing the efficiency of our method which improves the previous results on this problem.